để đánh một quyển sách người ta cần dùng 384 lượt chữ số a Tìm số trong cuốn sách b chữ số thứ 300 là số mấy
giúp mình với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. This is the first time Khanh went to Japan .
=> Khanh hasn't gone to Japan before .
2. Uyen stared learning 2 weeks ago .
=> Uyen has learnt for 2 weeks .
3. My parents began drinking when it started to rain .
=> My parents have drunk since it started to rain .
4. Tung last had his car repaired when I left him .
=> Tung haven't had his car repaired since I left him.
5. When did she have it ?
=> How long have she had it ?
6. I haven't seen my grandfather for 2 months .
=> The last time I saw my grandfather was 2 months ago .
7. Gin hasn't taken a bath since Tuesday .
=> It is Tuesday since Gin took a bath .
Học tốt
1) Khanh hasn't gone to Japan before
2) Uyen has learnt English for 2 weeks
3) My parents have drunk since it started rain
4) Tung hasn't repaired his car since the last time I left him
5) How long is it since she have had it ?
6) The last time I saw my grandfather was 2 months ago
7) It is 6 days since the last time Gin took a bath
Các bạn ơi phần này có 30 người trả lời thì mình sẽ ra phần 2 nhé
a) 25/100 ; 12/100 và -35/100
b) -12/32 ; -10/32 và -11/32
Mk hơi mới nên không rõ cách viết
1)
a)\(\frac{25}{100};\frac{12}{100};\frac{-35}{100}\)b)\(\frac{-12}{32};\frac{-10}{32};\frac{-11}{32}\)
2)
a)\(\frac{-1}{2}\&\frac{-4}{5}\) b)\(\frac{-6}{7}\&\frac{-7}{8}\) c)\(\frac{17}{200}\&\frac{17}{314}\)
\(\Rightarrow=\frac{-5}{10}\&\frac{-8}{10}\) \(\Rightarrow=\frac{-48}{56}\&\frac{-49}{56}\) Mà\(200< 314\)
Mà\(\frac{-5}{10}>\frac{-8}{10}\) Mà\(\frac{-48}{56}>\frac{-49}{56}\) \(\Rightarrow\frac{17}{200}>\frac{17}{314}\)
\(\Rightarrow\frac{-1}{2}>\frac{-4}{5}\) \(\Rightarrow\frac{-6}{7}>\frac{-7}{8}\)
a) \(x^5-x^4-1\)
\(=\left(x^5+x^2\right)-\left(x^4+x\right)-\left(x^2-x+1\right)\)
\(=x^2\left(x^3+1\right)-x\left(x^3+1\right)-\left(x^2-x+1\right)\)
\(=x^2\left(x+1\right)\left(x^2-x+1\right)-x\left(x+1\right)\left(x^2-x+1\right)-\left(x^2-x+1\right)\)
\(=\left(x^2-x+1\right)\left(x^3+x^2-x^2-x-1\right)\)
\(=\left(x^2-x+1\right)\left(x^3-x-1\right)\)
b) \(x^8+x^7+1\)
\(=\left(x^8-x^2\right)+\left(x^7-x\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x^6-1\right)+x\left(x^6-1\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x^3-1\right)\left(x^3+1\right)+x\left(x^3-1\right)\left(x^3+1\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)\left(x^3+1\right)+x\left(x-1\right)\left(x^2+x+1\right)\left(x^3+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left[\left(x^3-x^2\right)\left(x^3+1\right)+\left(x^2-x\right)\left(x^3+1\right)+1\right]\)
\(=\left(x^2+x+1\right)\left[\left(x^3-x\right)\left(x^3+1\right)+1\right]\)
\(=\left(x^2+x+1\right)\left(x^6-x^4+x^3-x+1\right)\)
Tính
\(E=1-2+3-4+5-6+...+71-72\)
\(=\left(1-2\right)+\left(3-4\right)+\left(5-6\right)+...+\left(71-72\right)\) (có 36 cặp)
\(=\left(-1\right)+\left(-1\right)+\left(-1\right)+...+\left(-1\right)\)
\(=\left(-1\right).36=-36\)
Vậy \(E=-36\).
Ta có: E=1-2+3-4+5-6+...+71-72
=> E=(1-2)+(3-4)+(5-6)+...+(71-72)
=> E= (-1)+(-1)+(-1)+...+(-1)
Dãy trên có số sô hạng là: (72-1):1+1=72 (số hạng)
Có số cặp là: 72:2=36(cặp)
=> E=(-1) x 36=-36
Áp dụng phương pháp hệ số bất định để phân tích \(x^4-2x^3-x^2-2x+1\)thành nhân tử.
Phân tích được là: \(\left(x^2-3x+1\right)\left(x^2+x+1\right)\)
=> \(\left(x^2-3x+1\right)\left(x^2+x+1\right)=0\)
Vì \(\left(x^2+x+1\right)>0\Rightarrow x^2-3x+1=0\)
\(\Rightarrow x^2-2.\frac{3}{2}x+\frac{9}{4}=\frac{5}{4}\Rightarrow\left(x-\frac{3}{2}\right)^2=\frac{5}{4}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{\sqrt{5}}{2}+\frac{3}{2}\\x=\frac{-\sqrt{5}}{2}+\frac{3}{2}\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{\sqrt{5}+3}{2}\\x=\frac{-\sqrt{5}+3}{2}\end{cases}}}\)
\(Q=\frac{1+\text{ax}}{1-\text{ax}}\sqrt{\frac{1-bx}{1+bx}}\)
Ta có: \(x=\frac{1}{a}\sqrt{\frac{2a-b}{b}}\Rightarrow\text{ax}=\sqrt{\frac{2a-b}{b}}\Rightarrow1+\text{ax}=1+\sqrt{\frac{2a-b}{b}}=\frac{\sqrt{b}+\sqrt{2a-b}}{\sqrt{b}}\)
\(1-\text{ax}=\frac{\sqrt{b}-\sqrt{2a-b}}{\sqrt{b}}\)
\(\Rightarrow\frac{1+\text{ax}}{1-\text{ax}}=\frac{\sqrt{b}+\sqrt{2a-b}}{\sqrt{b}-\sqrt{2a-b}}=\frac{\left(\sqrt{b}+\sqrt{2a-b}\right)^2}{2b-2a}\left(1\right)\)
\(bx=\frac{b}{a}\sqrt{\frac{2a-b}{b}}=\frac{\sqrt{b}\left(2a-b\right)}{a}\Rightarrow\hept{\begin{cases}1-bx=\frac{a-\sqrt{b\left(2a-b\right)}}{a}\\1+bx=\frac{a+\sqrt{b\left(2a-b\right)}}{a}\end{cases}}\)
\(\Rightarrow\frac{1-bx}{1+bx}=\frac{a-\sqrt{b\left(2a-b\right)}}{a+\sqrt{b\left(2a-b\right)}}=\frac{\left(a-\sqrt{b\left(2a-b\right)}\right)^2}{a^2-2ab+b^2}=\frac{\left(a-\sqrt{b\left(2a-b\right)}\right)^2}{\left(a-b\right)^2}\left(2\right)\)
Từ (1) và (2) \(\Rightarrow Q=\frac{\left(\sqrt{b}+\sqrt{2a-b}\right)^2}{2\left(b-a\right)}.\frac{a-\sqrt{b\left(2a-b\right)}}{a-b}=\frac{\text{[}2a+2\sqrt{b\left(2a-b\right)}\text{]}\left(a-b\sqrt{2a-b}\right)}{2\left(a-b\right)^2}\)
\(\Rightarrow\frac{2\left[a^2-b\left(2a-b\right)\right]}{2\left(a-b\right)^2}=\frac{2\left(a^2-2ab+b^2\right)}{a\left(a-b\right)^2}=1\)
Bài 1 đề nghị sửa lại : tổ III ủng hộ ít hơn tổng số tiền tổ I và tổ II ủng hộ là 72000đ
Ta có : x2 - 2x + 10 = 0
=> x2 - 2x + 1 = -9
=> (x - 1)2 = -9
=> \(x\in\varnothing\)
\(x^2-2x+10=0\)
\(\Leftrightarrow x^2-2x+1+9=0\)
\(\Leftrightarrow\left(x-1\right)^2+9=0\)
Mà \(\hept{\begin{cases}\left(x-1\right)^2\ge0\\9>0\end{cases}}\)
=> Phương trình vô nghiệm